rbcS genes in Solanum tuberosum: conservation of transit peptide and exon shuffling during evolution. - Wolter, F P (1988)
Five genes of the rbcS gene family of Solanum tuberosum (potato) were studied. One of these is a cDNA clone; the other four are located on two genomic clones representing two different chromosomal loci containing one (locus 1) and three genes (locus 2), respectively. The intron/exon structure of the three genes in locus 2 is highly conserved with respect to size and position. These genes contain two introns, whereas the gene from locus 1 contains three introns. Although in most cases the amino acid sequences in the transit peptide part of different rbcS genes from the same species varied considerably more than the corresponding mature amino acid sequences, one exception found in tomato and potato indicates that the transit peptide of rbcS could have a special function. A comparison of the rbcS genes of higher plants with those of prokaryotes offers suggestive evidence that introns first served as spacer material in the process of exon shuffling and then were removed stepwise during the evolution of higher plants.